Children’s Gothic: An Interview with Michael Howarth - Orrù, Marica; Howarth , Michael (REDEN. Revista Española de Estudios Norteamericanos, 2022)
Michael Howarth is a Professor of English at Missouri Southern States University and his main teaching areas are creative writing, film studies, American literature to the 1900s, British literature of the 19th century and children’s and young adult literature. He is also an author of both fiction and critical texts such as Under the Bed, Creeping: Psychoanalyzing the Gothic in Children’s Literature (2014) and Movies to See Before You Graduate from High School (2019), which is an analysis of 60 movies that he considers essential viewing for teenagers. He is also an author of fiction: in 2016 he published Fair Weather Ninjas, a young adult novel, and in 2021 his first Gothic novel titled A Still and Awful Red. He is a member of the Children’s Literature Association and the Southwest Texas Popular Culture and American Culture Associations, as well as Sigma Tau Delta.